2011
DOI: 10.1117/12.878502
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of vertical and horizontal circular C-arm trajectories

Abstract: C-arm angiography systems offer great flexibility in the acquisition of trajectories for computed tomography. Theoretically, these systems are able to scan patients while standing in an upright position. This would allow novel insights into structural changes of the human anatomy while weight bearing. However, this would require a scan on a horizontal trajectory parallel to the ground floor which is currently not supported by standard C-arm CT acquisition protocols.In this paper, we compared the standard verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…In evaluation of human subjects, the feasibility for CT reconstruction was demonstrated using a rotational angiogram in standing position, i.e., weight-bearing position. 1 Novel dedicated conebeam CT (CBCT) systems for orthopedics have also been developed to acquire weight-bearing imaging of the lower extremities. 2,3 CBCT systems with a flat panel provide superior spatial resolution with wide volumetric beam coverage along the axial direction compared to conventional CT, which allows high-resolution 3D images of entire knee in a single sweep without table translating per rotation.…”
Section: Introductionmentioning
confidence: 99%
“…In evaluation of human subjects, the feasibility for CT reconstruction was demonstrated using a rotational angiogram in standing position, i.e., weight-bearing position. 1 Novel dedicated conebeam CT (CBCT) systems for orthopedics have also been developed to acquire weight-bearing imaging of the lower extremities. 2,3 CBCT systems with a flat panel provide superior spatial resolution with wide volumetric beam coverage along the axial direction compared to conventional CT, which allows high-resolution 3D images of entire knee in a single sweep without table translating per rotation.…”
Section: Introductionmentioning
confidence: 99%
“…34 However, both trajectories showed comparable reproducibility over multiple scans acquired within one day and across one week. 34 As long as the trajectory is reproducible, we can geometrically calibrate the system using the projection matrix approach.…”
Section: Discussionmentioning
confidence: 99%
“…34 However, both trajectories showed comparable reproducibility over multiple scans acquired within one day and across one week. 34 As long as the trajectory is reproducible, we can geometrically calibrate the system using the projection matrix approach. The amount of wobble of the C-arm gantry should not impact the performance of the proposed subject-motion correction methods since the projection matrices are properly incorporated into the governing equations, Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the focus is on imaging the body in an upright position, as this is also the position in which the surgery is performed. 9 Maier et al 10 showed that C-arm CT devices allow horizontal trajectories. This renders medical examination of the weight-bearing knees possible with already available devices (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1). 10,15 Currently, these trajectories and their reconstruction methods are designed for circular FOVs, but many anatomical structures may be better described by a noncircular boundary, e.g., an ellipse.…”
Section: Introductionmentioning
confidence: 99%